Design of a Multiband Full-Rate Ultra-Wideband Receiver in FPGA - Véstias, Mário (2013)
MultiBand OFDM (MB-OFDM) UWB [1] is a short-range promising wireless technology for high data rate communications up to 480 Mbps. In this paper, we have designed and implemented in an Virtex-6 FPGA an MB-OFDM UWB receiver for the highest data rate of 480 Mbps. To test the system, we have also implemented an MB-OFDM transmitter and an AWGN generator in VHDL and determined the bit error rates at the receiver running in an FPGA.